Pemodelan Pelepasan In Vitro Tablet Floating Teofilin Dengan Program Ddsolver - Agus Siswanto; Indri Hapsari; Yusni Ulfiani Zulaikha; Eva Rosmawati (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2016)
ABSTRAK Disolusi merupakan elemen penting dalam pengembangan obat terutama terkait dengan absorpsi dan bioavailabilitas sediaan. Penelitian ini bertujuan untuk menentukan kinetika pelepasan tablet floating teofilin secara in vitro. Tablet floating teofilin dibuat dengan metode granulasi basah menggunakan bahan tambahan HPMC K4M CR, NaHCO3, laktosa, dan magnesium stearat. Hasil evaluasi sifat fisik menunjukkan bahwa tablet floating teofilin mempunyai bobot yang seragam (CV=1,93%), kekerasan yang baik (8,4 kg), dan kerapuhan yang rendah (0,05%). Evaluasi model pelepasan dengan program DDSolver menggunakan 2 kriteria: 1). Parameter statistik: R2adjusted, mean square error (MSE), weighted sum of squares (WSS), akaike information criterion (AIC), model selection criterion (MSC); 2). Visual goodness of fit (GOF). Hasil evaluasi data disolusi dengan program DDSolver menunjukkan bahwa pelepasan tablet floating teofilin mengikuti persamaan Weibull. Kurva disolusi berbentuk eksponensial dan pelepasan teofilin terjadi melalui mekanisme difusi. Kata kunci: tablet floating teofilin, DDSolver, pemodelan pelepasan obat. ABSTRACT The dissolution is an important element in drug development is mainly related to the absorption and bioavailability. The aim of this study was to determine in vitro dissolution study of theophylline floating tablet release kinetics model. The floating tablets were prepared by a wet granulation method with HPMC K4M CR, NaHCO3, lactose, and magnesium stearate as excipients. The result showed that the theophylline floating tablets had a weight uniformity (CV=1.93%), good hardness (8.4 kg), and low friability (0.05%). Dissolution data were evaluated using DDSolver conducted by 1). Statistical parameters: R2adjusted, mean square error (MSE), weighted sum of squares (WSS), akaike information criterion (AIC), model selection criterion (MSC); 2). Visual goodness of fit (GOF). The results showed that theophylline floating tablets release kinetics followed the Weibull equation. The dissolution curve is exponential shape and theophylline release occurs through a diffusion mechanism. Key words: floating tablet of theophylline, DDSolver, modeling of drug release.